Analysis of Integration Technological Pedagogical Content Knowledge (TPCK) of Preservice Mathematics Teacher in Planning the Learning Process - Suripah Suripah; Endang Istikomah; Nur Atiqah (AL-ISHLAH: Jurnal Pendidikan, 2025)
Professional teachers must master pedagogical and technological content knowledge (TPCK) to innovate in teaching. However, many teachers struggle to integrate technology effectively. Preparing preservice teachers with these skills is essential for their readiness in the workforce. This study analyzes the ability of preservice mathematics teachers to integrate technology into pedagogical content knowledge when planning mathematics lessons. This research employs a descriptive qualitative approach. The subjects were 23 fifth-semester preservice mathematics teachers from Universitas Islam Riau. TPCK analysis was conducted on their lesson planning documents, focusing on three aspects: Technological Knowledge (TK), Technological Content Knowledge (TCK), and Technological Pedagogical Knowledge (TPK). Data analysis followed four stages: data collection, reduction, presentation, and verification. Findings indicate that preservice teachers demonstrated very good competency in technological knowledge (TK) when designing learning plans. Their ability to integrate technology with subject content (TCK) was rated as good. Similarly, their understanding of using technology in pedagogy (TPK) was also classified as good. These results suggest that preservice mathematics teachers are capable of integrating technology into pedagogical content knowledge effectively, though there is room for improvement in refining their strategies. Preservice teachers exhibit good competence in TPCK when designing mathematics lesson plans, highlighting their readiness to apply technology in future teaching. Further research should explore strategies to enhance their technological integration skills in practical teaching settings.